The Effect of NaOH on the Synthesis of Nano ZnO Using Red Betel Leaves (Piper crocatum) by Green Synthesis Method - Nurcahayaniati, Hikmah; Manurung, Posman; Suciyati, Sri Wahyu; Asmi, Dwi (Journal of Energy, Material, and Instrumentation Technology, 2025)
ZnO has been produced using a green synthesis method. This research aims to determine the effect of  NaOH variations on ZnO nanoparticles obtained using red betel leaf extract. The variation of  NaOH used is 0,2; 0,4; 0,6;  the characterization carried out was Fourier Transformation Infra Red (FTIR), X-Ray Difraction (XRD),   Scanning Electron  Microscopy (SEM), dan Ultra Violet Vissible (UV DRS) the results of FTIR  characterization show that the functional groups in red betel leaves play a role in the information of  ZnO nanoparticles, XRD characrerization shows diffraction peaks of ZnO nanoparticles and the presence of NaNO3 phase at 0,2; 0,4; 0,6; and 1 M variation. Then, the SEM results showed a spherical morphology at a 1 M variation, and the UV-DRS results showed an absorption peak at 331 nm and a band gap energy of 3.11 eV.